Diversity, relative abundance and activity patterns of medium and large mammals in a tropical deciduous forest in the Isthmus of Tehuantepec, Oaxaca, Mexico - Cortés-Marcial, Malinalli; Briones-Salas, Miguel (Revista de Biología Tropical, 2014)
The use of camera traps and mammal track search are complementary methods to monitoring species of which is not well documented their natural history, as in the case of medium and large mammals. To ensure its conservation and good management, it is necessary to generate information about the structure of the community and their populations. The objective of the present study was to estimate the diversity, relative abundance and activity patterns of medium and large mammals in a tropical deciduous forest located in the Isthmus of Tehuantepec, Oaxaca, Mexico. Samplings were conducted in three month intervals, from September 2011 to May 2013. We used photographic-sampling and track search, two complementary sampling methods. For photographic-sampling, 12 camera traps were placed covering an area of 60km2, while for the tracks search a monthly tour of four line-transect surveys of three kilometers length each was undertaken. We obtained a total of 344 pictures with 5 292 trap-days total sampling effort; in addition, 187 track records in a total of 144km. With both methods we registered 21 species of mammals, in 13 families and seven orders, and five species resulted in new records to the area. The diversity index of Shannon-Wiener obtained with the method of tracks was H´=2.41, while the most abundant species were Urocyon cinereoargenteus (IAR=0.23) and Pecari tajacu (IAR=0.20). By the method of trap the most abundant species were P. tajacu (IAR=2.62) and Nasua narica (IAR=1.22). In terms of patterns of activity P. tajacu, N. narica and Odocoileus virginianus were primarily diurnal species; Canis latrans and Leopardus pardalis did not show preference for any schedule in particular, and Didelphis virginiana and Dasypus novemcinctus preferred to have nocturnal activity. This information can be of help to the creation of programs of management and conservation of mammals of medium and large in the Isthmus of Tehuantepec, Oaxaca, México.